2017
DOI: 10.1111/1460-6984.12348
|View full text |Cite
|
Sign up to set email alerts
|

Oral and written picture description in individuals with aphasia

Abstract: The analysis of both modalities (speech and writing) at the discourse level allows one to assess simultaneously micro- and macro-linguistic skills and their potential interrelations in a given IWA. Connected writing appears to be more sensitive in discriminating IWA from healthy controls than connected speech. This method for analyzing language samples should, however, be used in conjunction with other assessment tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
(107 reference statements)
0
18
0
Order By: Relevance
“…Scoring can be done according to the manual or more thoroughly according to the variables mentioned by Vandenborre et al . 20 To assess word retrieval, various object naming tests are used: BNT (Boston Naming Test), DuLIP (Dutch Linguistic Intraoperative Protocol) and VAN-POP (Verb and Noun test for Perioperative Testing).…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Scoring can be done according to the manual or more thoroughly according to the variables mentioned by Vandenborre et al . 20 To assess word retrieval, various object naming tests are used: BNT (Boston Naming Test), DuLIP (Dutch Linguistic Intraoperative Protocol) and VAN-POP (Verb and Noun test for Perioperative Testing).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The picture description test, a subtest from the CAT-NL (Comprehensive Aphasia Test-Netherlands), is used to assess semispontaneous speech in an oral and written way (5 min each condition). Scoring can be done according to the manual or more thoroughly according to the variables mentioned by Vandenborre et al 20. To assess word retrieval, various object naming tests are used: BNT (Boston Naming Test), DuLIP (Dutch Linguistic Intraoperative Protocol) and VAN-POP (Verb and Noun test for Perioperative Testing).…”
Section: Methods and Analysismentioning
confidence: 99%
“…For example, studies have shown that PWAs produce more spelling errors in text than a reference group (Vandenborre et al . 2018) and tend to avoid words that they find difficult to spell (Johansson‐Malmeling et al . 2020), and that this tendency affects certain lexical features (word use) of their texts (Johansson‐Malmeling 2019), which may have an impact on overall text quality.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific investigation of spelling difficulties caused by aphasia has tended to be based mainly on single-word-dictation tasks (Beeson and Rapcsak 2015), but spelling difficulties have also been found to negatively affect aspects of text writing in persons with aphasia (PWAs). For example, studies have shown that PWAs produce more spelling errors in text than a reference group (Vandenborre et al 2018) and tend to avoid words that they find difficult to spell (Johansson-Malmeling et al 2020), and that this tendency affects certain lexical features (word use) of their texts (Johansson-Malmeling 2019), which may have an impact on overall text quality. To successfully treat PWAs and/or develop digital tools to facilitate their writing and spelling, it is crucial to increase knowledge about the nature of their difficulties not only with spelling but also with editing.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the nondominant hemisphere, mostly preserved in PWA, is mainly responsible for visuo-spatial processing (Brown and Thiessen 2018). Hence, using a picture for spontaneous language production encourages PWA to retrieve the concepts and associated functions present in the picture stimulus (Vandenborre et al 2018). Therefore, it is necessary to choose an appropriate picture stimulus for PDT.…”
Section: Introductionmentioning
confidence: 99%